2023
DOI: 10.4269/ajtmh.22-0532
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Profiles and Zinc Supplementation among Children with Diarrhea in Bangladesh

Abstract: Zinc supplementation is an added intervention with oral rehydration solution (ORS) for treating childhood diarrhea as per World Health Organization recommendations. Our study aimed to determine the prevalence of zinc administration in addition to ORS for childhood diarrhea before hospitalization and the nutritional profile of those children admitted to the outpatient department of the largest diarrheal facility in Bangladesh. This study used a screening dataset of a clinical trial (www.clinicaltrials.gov; NCT0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…16 A study conducted on zinc supplementation at a Dhaka hospital (International Centre for Diarrhoeal Disease Research, Bangladesh) indicated that dehydration, bloody diarrhoea and fever were less with those under 5 children received a zinc for diarrhoea at home. 17 However, the global prevalence of using ORS with zinc to treat diarrhoea continues to be alarmingly low. 2 Less than 7% of children under the age of 5 in low-income and middle-income countries (LMICs) receive zinc treatment, according to a 2017 UNICEF report, and only 44% of them receive ORS.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
See 1 more Smart Citation
“…16 A study conducted on zinc supplementation at a Dhaka hospital (International Centre for Diarrhoeal Disease Research, Bangladesh) indicated that dehydration, bloody diarrhoea and fever were less with those under 5 children received a zinc for diarrhoea at home. 17 However, the global prevalence of using ORS with zinc to treat diarrhoea continues to be alarmingly low. 2 Less than 7% of children under the age of 5 in low-income and middle-income countries (LMICs) receive zinc treatment, according to a 2017 UNICEF report, and only 44% of them receive ORS.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…Zinc supplementation lessens the length and intensity of episodes and lowers the likelihood of recurrence in the short term,14 15 ORS contains trisodium citrate dehydrate, glucose, sodium chloride and potassium chloride which is important to replenishes the vital fluids and salts lost via diarrhoea 16. A study conducted on zinc supplementation at a Dhaka hospital (International Centre for Diarrhoeal Disease Research, Bangladesh) indicated that dehydration, bloody diarrhoea and fever were less with those under 5 children received a zinc for diarrhoea at home 17…”
Section: Introductionmentioning
confidence: 99%